RETRACTED: Providing thermal exchange when designing special clothing - Mirtalipova N.; Kamilova Kh.; Vakhidova U. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001